KAJIAN PENGARUH PENERAPAN ARSITEKTUR TROPIS TERHADAP KENYAMANAN TERMAL PADA BANGUNAN PUBLIK MENGGUNAKAN SOFTWARE ECOTECH Studi kasus: Perpustakaan Universitas Indonesia - Susilowati, Diana; Wahyudi, Feri (Jurnal Ilmiah Desain & Konstruksi, 2014)
The sustainable of an architectural work for the community and the surrounding environment provides a discussion on the design and application of contextual with the built environment. In this case study case in point is the Library of the University of Indonesia. The building was chosen because it is considered to represent the concept of tropical architecture. The problems discussed in this study include; how the concept of tropical architecture is applied in the library and want to know how they affect the concept of the thermal comfort in buildings. In this study the method used to describe and review all the data and other information, from direct observation or indirectly. This analysis uses quantitative analysis by comparing the existing situation in the field with the study and the information obtained from the literature as well as qualitative analysis as it relates to the amount of space that is used in analyzing the use of software Ecotech. This study is expected to reference input regarding the thermal comfort of a building which is calculated using a software-assisted.Keywords: tropical architecture, thermal comfort, EcoTech